The possibilities of assessing the efficacy and comparison of the license plate recognition systems - Rychlicki, Mariusz; Kwiatkowski, Tomasz (Roads and Bridges – Drogi i Mosty, 2015)
The paper consists of a review and the characteristics of contemporary methods of vehicle registration plate recognition. Their high and increasingly growing importance for the use in intelligent transport systems has been discussed. Their large impact on improving traffic safety and the development of related systems, such as weighing vehicles in motion, have been emphasized. Attention has been paid to the existing problems in the evaluation of the effectiveness and comparison of such systems. The nature of the problem has been indicated, which consists in the fact that manufacturers and suppliers of such solutions overrate the effectiveness of the recognition, declared to be even 100%. For obvious reasons, it raises questions and poses practical problems. For this reason, the paper presents a method for assessing the license plate recognition systems, which might contribute to their practical comparison and determination of the real level of effectiveness. The implementation of the method in the tool application has been performed and the analysis of the obtained results has been carried out. A design of the test stand has been proposed, that would enable the evaluation of such solutions in the laboratory conditions.